(untitled) (Medico Legal Update, 2020)
Introduction: All through the world, induction of labour fails in 20% of cases and thus cesarean section is performed. Obesity is a risk factor for undesired results of pregnancies. Although the Bishop score is simple and easy to apply, it is a subjective evaluation method and results may vary according to the clinical experience of the person applying it. Transvaginal cervical measurement can be more objective criterion in assessing the success of labor induction. We aimed to identify the proper characteristics of the pregnant women, which can go for successful induction of labour. Method: Induction of labor for 100 women using vaginal misoprostol was done following identification of their BMI, modified bishop score and transvaginal cervical length. All women were pregnant ?38 weeks, singleton, cephalic presentation, intact fetal membranes. Results: About 92 women had successful induction of labour (group 1) while the remaining eight women had failed induction (group 2). BMI did not show statistical significance however, the modified Bishop score and the transvaginal cervical length showed high statistical significance. Using the modified bishop score 2 as a cutoff value showed sensitivity 89.1%, and specificity 62.5% while using the transvaginal cervical length 2.65 as a cutoff value showed sensitivity 72.8% and specificity 100%. Conclusion: Induction of labour by vaginal misoprostol is very promising in term women providing identification of their modified Bishop score and their transvaginal cervical length.